2012
DOI: 10.1177/0264550511429844
|View full text |Cite
|
Sign up to set email alerts
|

Promoting offender engagement and compliance in sentence planning: Practitioner and service user perspectives in Hertfordshire

Abstract: The following article is based on research in Hertfordshire regarding sentence planning and offender engagement, undertaken with the support of a Graham Smith bursary. The findings suggest that interpersonal contact and relationships between service users and practitioners are of most significance in encouraging compliance and engagement. This in turn suggests that interactional practice skills should be the key focus of future training and development of staff, in terms of enabling them to plan with service u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…But, there has been limited analysis of the extent of service user participation in community justice settings, and the impact on compliance. The few studies of service user participation during probation supervision have found limited evidence that service users participate in the design and implementation of service delivery (see, for example, Hughes ). Equally, the few existing studies of compliance with community‐based orders indicate that service users tend to play a minor role in producing compliance (Phillips ; Ugwudike ; Weaver and Barry ).…”
Section: The Extent Of Service User Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…But, there has been limited analysis of the extent of service user participation in community justice settings, and the impact on compliance. The few studies of service user participation during probation supervision have found limited evidence that service users participate in the design and implementation of service delivery (see, for example, Hughes ). Equally, the few existing studies of compliance with community‐based orders indicate that service users tend to play a minor role in producing compliance (Phillips ; Ugwudike ; Weaver and Barry ).…”
Section: The Extent Of Service User Participationmentioning
confidence: 99%
“…Other studies have also found links between limited participation and lack of engagement during supervision. Hughes (, p.63) found in a study of service users’ engagement with the sentence planning process, that although some of the participating probationers reported that they were willing to attend appointments, they were motivated mainly by instrumental reasons; primarily the requirement placed on them to attend and the ‘benefit’ they sought to achieve from supervision. The study noted that service user participation in sentence planning was limited.…”
Section: Implications Of Limited Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of the value of lived experiences in justice settings is not an isolated development, rather it forms part of an increasing emphasis on service user engagement in human services, given the necessity for methods that better suit service users’ primary needs (Hughes ) and reduce the divisions between recipients and providers (Beresford , p.310). Simultaneously there has been a political drive to develop volunteering in criminal justice (Cabinet Office ; Ministry of Justice ).…”
mentioning
confidence: 99%
“…Community penalties require young people to do things (such as keeping appointments with YOT workers and participating in activities) that they may otherwise not have done and they may not respond well to threats (Canton, 2008). Conversely, interpersonal contact and relationships between service users and practitioners are deemed to be very important in encouraging compliance and engagement (Farrell, 2002a;Hughes, 2011;McNeill et al, 2005;Maruna, 2001). McNeill (2005) concludes that practitioners might usefully reflect on the importance of verbal messages which are relayed to those on community orders, and the way in which these are delivered.…”
mentioning
confidence: 99%